Pain Neuroscience Education in cancer survivors with persistent pain: A pilot study. Issue 4 (October 2020) - Pas, Roselien; Leysen, Laurence; De Goeij, Wanda; Vossebeld, Leonieke; Van Wilgen, Paul; De Groef, An; De Kooning, Margot
Abstract: Purpose: To describe the Pilot Study: Pain Neuroscience Education in Cancer Survivors and describe the innovative educational component of Pain Neuroscience Education (PNE). Design: Quasi experimental design. Method: The PNE program, encompassing a one-on-one education session and an information leaflet was given to 30 cancer survivors. At baseline and two weeks after the PNE, participants were asked to fill out following outcome measures; pain intensity, pain catastrophizing, and HRQoL. Findings: Following PNE, a significant decrease on pain intensity ( p  = 0.001), on the SF-36 subscale pain ( p  = 0.003) and for the following PCS subscales: Helplessness ( p  < 0.001), Rumination ( p  = 0.002) and Total score ( p  < 0.001) was found compared to baseline. Conclusions: Although the current results need to be verified in a larger randomized, controlled trial, preliminary evidence shows a decrease in pain intensity and pain catastrophizing following PNE in cancer survivors with persistent pain.